Prevalence and risk factors of overweight and obesity in adolescents - Gary Adhianto; Soetjiningsih Soetjiningsih (Indonesian Pediatric Society, 2002)
Background Overweight and obesity in adolescents is associated with persistent obesity and higher risk of morbidity and mortality in adulthood.Objective To determine the occurrence of overweight and obesity in adolescents and to identify the associated risk factors.Methods A cross sectional study was carried out on 600 dlildren aged from 11 to 17 years old. Anthropometric measurements induded body weight, height, and triceps skin fdd thickness. The nutritional status was dassified based on BMI using the WHO standard criteria. Three 24-hour dietary recalls were collected to assess the quality of food. A systematic random sampling was made according to school grade and sex.Results Five hundred and fifty two (92%) children met the indusion criteria, 46% were boys and 54% were girls. Most subjects (64%) had nonnal weight, 12% were underweight, 13% were overweight and 11% were obese. Among overweight group, 49% were boys, while among obese group, 53% were boys. On bivariate analysis, it was found that nutritional status had strong relationship with mother's education. On multivariate regression analysis, it was noted that energy expenditure and mother's education had significant negative correlation with the occurrence of overweight and obesity (8=- 0.235; p<0.001 and 8=-0.171; P=0.006) while energy intake and parental obesity had a significant positive correlation (8=0.498; P<0.001 and B=0.128; P<0.001).Conclusions Energy expenditure and mother's education were inversely related to overweight and obesity, while energy intake and parental obesity were proportionally related to overweight and obesity.